Business Communication in Improving the Entrepreneurial Skills of SME Members - Ratnasari, Anne; Sofyan, Aning; Yuniati, Yenni (KnE Social Sciences, 2023)
The Sapta Mandiri Entrepreneurs Association, representing Small and Medium Enterprises (SMEs) in Bandung Regency, stands out as an association of business actors that has successfully weathered the challenges posed by the Covid-19 pandemic. This association actively engages in business communication to enhance the entrepreneurial skills of its members. This article presents the findings of research conducted on this phenomenon. The primary objective of this research is to analyze the different types of business communication utilized, the factors influencing business communication, and the specific purposes behind such communication in improving the entrepreneurial skills of SME members. The research approach employed for this study is a case study, while data collection techniques include literature review, in-depth interviews, and observation. The research informants comprise administrators from the Sapta Mandiri Entrepreneurs Association. The results of the study reveal two main types of business communication practiced within the association of entrepreneurs: horizontal communication and vertical communication. Several factors have been identified to influence business communication, including perception, credibility, accuracy, suitability, and control. The primary purposes of business communication are to provide essential information, persuade members, and foster cooperation, thereby contributing to the enhancement of entrepreneurial skills among SME members. In conclusion, the Sapta Mandiri Entrepreneurs Association has demonstrated resilience during the Covid-19 pandemic by employing effective business communication strategies. This has enabled the association to support its members in enhancing their entrepreneurial skills and navigating through the challenging business landscape. Keywords: business communication, entrepreneurship, SME business people, the Covid-19 pandemic